Metal–organic frameworks as a platform for clean energy applications. Issue 2 (May 2020) - Li, Xinran; Yang, Xinchun; Xue, Huaiguo; Pang, Huan; Xu, Qiang
Highlights: The recent progress of the use of MOFs as a platform for clean energy, including physical hydrogen and methane storage, chemical hydrogen storage, solar energy conversion, and electrochemical conversion and storage, has been reviewed. The challenges and opportunities towards advanced energy technologies with the MOF-based materials for clean energy applications have been discussed. Abstract: Metal–organic frameworks (MOFs), an emerging class of porous materials, have shown intriguing and promising properties in a wide range of applications due to their versatile structures, large surface areas, tunable porosity and tailorable chemistry. In recent years one of the most active research fields is to explore energy applications of MOF-based materials. In this review, we present a critical overview on the recent progress of the use of MOF-based materials for gaseous fuel storage, chemical hydrogen storage, solar and electrochemical energy storage and conversion. The challenges and opportunities towards advanced energy technologies with the MOF-based materials are discussed. Graphical abstract: Image, graphical abstract